Pyridines from lab to production - Scriven, Eric F. V. (Amsterdam Elsevier, 2013)
Provides a synthetic armory of tools to aid the practicing chemist by reviewing the most reliable historical methods alongside new methods. Written by scientists who have actually used these in synthesis. By emphasizing tricks and tips to optimize reactions for the best yields and purity, which are often missing from the primary literature, this book provides another dimension for the synthetic chemist. A combined academic and industrial approach evaluates the best methods for different scales of reaction and discusses practical tips.
Includes bibliographical references and index.
Keywords: Pyridine